PENGARUH BAURAN PEMASARAN DAN KOMUNIKASI TERHADAP LOYALITAS NASABAH PADA PT. BANK MASPION INDONESIA, TBK CABANG MEDAN - Wily Julitawaty; Shelly Carolina; Thomas Sumarsan Goh (JURNAL BISNIS KOLEGA, 2019)
Abstract. In the development of the banking business at this time, marketing plays an important role for the business continuity and this should be supported by customer loyalty. Marketing mix and communication are the factors that influence customer loyalty in marketing a product. The purpose of this study is to find the relationship between marketing mix and communication towards customer loyalty. The research methodology that is being used to measure is by survey, the type of research is quantitative descriptive and the nature of this research is explanatory research. The populations in this research were customers of PT. Bank Maspion Indonesia, Tbk Medan Branch as many as 163 people with a sample of 116 people. The method of data collections are done by distributing questionnaires, interviews, and literature studies. The variable was measured by a Likert scale. The results showed that marketing mix and communication simultaneously have a significant affect on customer loyalty at PT. Bank Maspion Indonesia, Tbk Medan Branch. Partially, the marketing mix does not have a significant affect on customer loyalty at PT. Bank Maspion Indonesia, Tbk Medan Branch and communication has a significant affect on customer loyalty at PT. Bank Maspion Indonesia, Tbk Medan Branch.Keywords: Marketing Mix, Communication, Customer Loyalty.